Duct Stenting Versus Modified Blalock-Taussig Shunt in Neonates With Duct-Dependent Pulmonary Blood Flow: Associations With Clinical Outcomes in a Multicenter National Study. Issue 6 (6th February 2018) - Bentham, James R.; Zava, Ngoni K.; Harrison, Wendy J.; Shauq, Arjamand; Kalantre, Atul; Derrick, Graham; Chen, Robin H.; Dhillon, Rami; Taliotis, Demetris; Kang, Sok-Leng; Crossland, David; Adesokan, Akintayo; et al.
Abstract : Background: Infants born with cardiac abnormalities causing dependence on the arterial duct for pulmonary blood flow are often palliated with a shunt usually between the subclavian artery and either pulmonary artery. A so-called modified Blalock-Taussig shunt allows progress through early life to an age and weight at which repair or further more stable palliation can be safely achieved. Modified Blalock-Taussig shunts continue to present concern for postprocedural instability and early mortality such that other alternatives continue to be explored. Duct stenting (DS) is emerging as one such alternative with potential for greater early stability and improved survival. Methods: The purpose of this study was to compare postprocedural outcomes and survival to next-stage palliative or reparative surgery between patients undergoing a modified Blalock-Taussig shunt or a DS in infants with duct-dependent pulmonary blood flow. All patients undergoing cardiac surgery and congenital interventions in the United Kingdom are prospectively recruited to an externally validated national outcome audit. From this audit, participating UK centers identified infants <30 days of age undergoing either a Blalock-Taussig shunt or a DS for cardiac conditions with duct-dependent pulmonary blood flow between January 2012 and December 31, 2015. One hundred seventy-one patients underwent a modified Blalock-Taussig shunt, and in 83 patients, DS was attempted. Primary and secondary outcomes of survival and need for extracorporeal support were analyzed with multivariable logistic regression. Longer-term mortality before repair and reintervention were analyzed with Cox proportional hazards regression. All multivariable analyses accommodated a propensity score to balance patient characteristics between the groups. Results: There was an early (to discharge) survival advantage for infants before next-stage surgery in the DS group (odds ratio, 4.24; 95% confidence interval, 1.37–13.14; P =0.012). There was also a difference in the need for postprocedural extracorporeal support in favor of the DS group (odds ratio, 0.22; 95% confidence interval, 0.05–1.05; P =0.058). Longer-term survival outcomes showed a reduced risk of death before repair in the DS group (hazard ratio, 0.25; 95% confidence interval, 0.07–0.85; P =0.026) but a slightly increased risk of reintervention (hazard ratio, 1.50; 95% confidence interval, 0.85–2.64; P =0.165). Conclusions: DS is emerging as a preferred alternative to a surgical shunt for neonatal palliation with evidence for greater postprocedural stability and improved patient survival to destination surgical treatment. Abstract : Supplemental Digital Content is available in the text.